Enhancing magnetocaloric performance in Dy5−xHoxB2C5 (x = 0, 1, 2) compounds for hydrogen liquefaction - Haobo Sun; Lu Tian; Jianjian Gong; Zhenxing Li; Zhaojun Mo; Guodong Liu; Jun Shen (APL Energy, 2025)
Magnetic refrigeration based on the magnetocaloric effect has shown promising potential for hydrogen liquefaction. However, the lack of high-performance magnetic refrigerant materials operating in the liquid hydrogen temperature range significantly hinders the advancement of this technology. In this study, we systematically investigated the crystal structure, electronic structure, magnetism, and magnetocaloric properties of Dy5−xHoxB2C5 compounds, a member of the rare-earth boron–carbon family, through theoretical calculations and experimental analysis. The substitution of Ho for Dy leads to a reduction in the total spin quantum number of the system, resulting in a progressive decrease in the magnetic transition temperature from 70 to 60 and 50 K with increasing Ho content. Furthermore, the enhanced magnetocaloric effect observed in these compounds is attributed to the increased saturation magnetization induced by Ho substitution. These findings suggest that the Dy5−xHoxB2C5 series holds significant promise as a magnetic refrigerant for hydrogen liquefaction applications.